Demographic and Clinical Differences Between Bipolar Disorder Patients With and Without Alcohol Use Disorders - Xia, Yan; Ma, Dongying; Perich, Tania; Hu, Jian; Mitchell, Philip B. (Frontiers in Psychiatry, 2020)
Background: Bipolar disorder (BD) and alcohol use disorder (AUD) are two major independent causes of psychopathology in the general population. The prevalence of AUD in BD is high. Identifying the clinical and demographic features of patients with BD who may develop AUD could help with early identification and intervention. Methods: Data from 238 patients diagnosed with BD were gathered on alcohol use, social demographics, longitudinal course of BD, clinical features of the most severe lifetime manic and depressive episodes, comorbid physical diseases, anxiety disorders, and other substance use disorders. Results: We found that 74 of 238 BD patients had AUD (67 with alcohol dependence and 7 with alcohol abuse). Bivariate logistic regression analysis and multivariate logistic regression analysis found that the best predictors of AUD in patients with BD were being male (OR = 2.086, 95% CI = 1.094-3.979, p = 0.001), younger (OR = 0.965, 95% CI = 0.935-0.996, p = 0.026), and comorbidity with other unclassified substance dependence (OR = 10.817, 95% CI = 1.238-94.550, p = 0.031). Conclusions: Male, younger current age, and having other substance use disorders were independently associated with AUD.